P2_9 Antimatter Propulsion - Anand, Jasdeep; Weaver, Iain; Gorley, Michael; Buccheri, Alex (Physics Special Topics, 2009)
<span style="font-size: 10pt; font-family: ";Calibri";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-bidi-font-family: 'Times New Roman'; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">A method of using matter-antimatter annihilation to power a spacecraft via propellant heating is discussed in this paper. Using Tsiolkovsky’s rocket equation it is determined that such a spacecraft would require approximately 4 times its mass as propellant, which would greatly improve the craft-to-fuel mass carried by current missions.